This page requires a JavaScript-enabled browser
Instructions on how to enable your browser are contained in the help file.
Math 10 Chapter 2 - Part D
1.
If x/a = b and a/x = c then bc = _________________
a) 0
b) 1/a
c) 1
d) a
2.
Eliminating z from z
^{2}
+ 1/z
^{2}
= n
^{2}
and z + 1/z = m we get
a) n
^{2}
| m
^{2}
= -2
b) n
^{2}
| m
^{2}
= 2
c) n
^{2}
+ m
^{2}
=2
d) n
^{2}
+ m
^{2}
= -2
3.
Eliminating z from z | 1/z = 5a and z
^{2}
+ 1/z
^{2}
= 10 we get
a) a
^{2}
=8
b) a
^{2}
= 12
c) 25a
^{2}
= 12
d) 25a
^{2}
=8
4.
Eliminating m from m
^{2}
= y/2 and m
^{4}
= 3x we get
a) y
^{2}
= 12x
b) x
^{2}
= 12y
c) y
^{2}
= x
d) x
^{2}
= y
5.
Eliminating 'y' from y = 2t and y = 2s we get
a) 4t = s
b) s = 2t
c) 4s = t
d) s = t
6.
Eliminating 'y' from y= 1/2t and y = 2s we get
a) s =t
b) st = 4
c) s = 4t
d) 4st = 1
7.
The relation free from 't' fro t
^{2}
= 1/x and t
^{3}
= 2y is
a) y
^{3}
= 4x
^{2}
b) x
^{3}
= 4y
^{2}
c) 4x
^{2}
y
^{3}
= 1
d) 4x
^{3}
y
^{2}
= 1
8.
The relation free from 't' for x + 2t = p and y-3t = p is
a) 3x + 2y = p
b) 2x | 3y = 5p
c) 3x+2y = 5p
d) 3x-2y = p
9.
The eliminant by eliminating 'm' for equations m + x = 3s and m | y = -8s is
a) x + y = 11s
b) x-y = 11s
c) x + y= 5s
d) x � y = 5s
10.
The relation free from 'y' for y = 2/s and y= t/2 is
a) st = 2
b) s = 4t
c) s =t
d) st = 4
11.
The relation free from 'u' for u = 2/x and y= 2/u
a) x=2y
b) y= x
c) y = 2x
d) y= 4x
12.
The relation free from 'u' for u = 2/tand u = 1/2s is
a) 4s = t
b) t = s
c) 4t = s
d) t = 2s
13.
at = x bt = y
a) a
^{2}
= b
^{3}
b) bx = ay
c) x-y = a-b
d) a
^{3}
= b
^{2}
14.
at
^{2}
= x bt
^{3}
= y
a) b
^{2}
x
^{3}
= a
^{3}
y
^{2}
b) c
^{3}
b
^{5}
=a
^{5}
d
^{3}
c) a
^{2}
= b
^{3}
d) c
^{3}
d
^{5}
= a
^{5}
b
^{3}
15.
a-t
^{2}
= 0 b = t
^{3}
a) a
^{3}
= b
^{2}
b) b
^{2}
x
^{3}
= a
^{3}
y
^{2}
c) a
^{2}
= b
^{3}
d) c
^{3}
b
^{5}
=a
^{5}
d
^{3}
16.
ct
^{5}
= d at
^{3}
= b
a) c
^{3}
b
^{5}
=a
^{5}
d
^{3}
b) a
^{2}
= b
^{3}
c) a
^{3}
= b
^{2}
d) b
^{2}
x
^{3}
= a
^{3}
y
^{2}
17.
x + t = a y+ t =b
a) b
^{2}
x
^{3}
= a
^{3}
y
^{2}
b) x-y = a-b
c) a
^{3}
= b
^{2}
d) a
^{2}
= b
^{3}
18.
x + 1/x = n x
^{2}
+ 1/x
^{2}
=m
^{2}
a) n
^{2}
| m
^{2}
= 2
b) m
^{3}
| n
^{3}
= 3n
c) b
^{2}
| a
^{2}
= 4
d) m
^{2}
| n
^{2}
= 4
This is more feedback!
This is the feedback!